Impact of Covid-19 Pandemic on Education in India: A Case Study - KUMAR, MR. MANISH (The journal of contemporary issues in business and government, 2021)
The whole world has been disrupted by the pandemic of Covid-19. The lockdown in various countries has immensely affected the education of students. Students can no longer interact with their teacher on one to one basis. This has caused a shift from the traditional classrooms learning to the computer based learning and it may be the largest change in the educational system till date. The online learning has become new normal in India due to pandemic, it becomes necessary to keep track of its growth & to find out whether it is capable of fulfilling student’s primary objective i.e. learning. Therefore, the present study was designed to understand and find out students point of view, perspective and objective on ground level. This study could be used in future to overcome the found limitations and help in implementing a more effective online education process for students of all levels.